Two New Species of Cnemaspis (Sauria: Gekkonidae) from Tamil Nadu, Southern India - Das, I.; Bauer, Aaron M. (Folium Publishing Company, 2000)
Two new species of Cnemaspis (Sauria: Gekkonidae) are described from peninsular India. Cnemaspis otai n.sp. occurs in the southern Eastern Ghats at Vellore. It is a small member of the genus (snout-vent length to 29.7 mm) diagnosable by the combination of characters: paired postmentals in broad contact; nostril not in contact with supralabial I; midventrals 18; dorsal tubercles isolated and scattered; no spine-like tuber - cles on flanks; ventrals smooth; four preanal and three femoral pores; tail with enlarged flattened scales forming whorls, supralabials to angle of jaws 7; narrow distal lamellae under digit IV of pes 13 – 15; dor - sum grayish-brown, with three pairs of partially fused, black paravertebral spots. Cnemaspis yercaudensis (snout-vent length 24.9 mm) is known from a single specimen taken at Yercaud in the Shevaroy Hills. It is diagnosed by the following characters: postmentals separated by a single scale; nostrils in contact with supralabial I; midventrals 22; no spine-like tubercles on flanks; ventrals smooth; two preanal and three fe - moral pores; narrow distal lamellae under digit IV of pes 11 – 12; dorsum grayish-brown, darkly mottled; ventrum and gular region yellowish-cream, unpatterned. The presence of a lateral pair of cloacal bones in these and other south Asian species of Cnemaspis may be synapomorphic and should be investigated fur- ther. These species are the first Indian Cnemaspis to be described from their respective hill ranges and help to fill the large gap (Western Ghats to southeastern Thailand) in the distribution of the genus as a whole.